2022
DOI: 10.3389/fimmu.2022.886468
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s disease recurrence updates: first surgery vs. surgical relapse patients display different profiles of ileal microbiota and systemic microbial-associated inflammatory factors

Abstract: Background and aimsCrohn’s disease (CD) pathogenesis is still unclear. Remodeling in mucosal microbiota and systemic immunoregulation may represent an important component in tissue injury. Here, we aim to characterize the ileal microbiota in both pathological and healthy settings and to evaluate the correlated systemic microbial-associated inflammatory markers comparing first-time surgery and relapse clinical conditions.MethodsWe enrolled 28 CD patients at surgery; we collected inflamed and non-inflamed mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 93 publications
2
11
0
4
Order By: Relevance
“…21 Our group have recently observed changes in the profiles of circulating FFA in various immune-mediated disorders, such as celiac disease, 19 systemic sclerosis 22 and Crohn's disease. 23 Likewise, our data have shown that the serum FFA signature in PV patients is significantly altered in comparison with the 'healthy profile' and displayed a shift towards a pro-inflammatory state. This 'pemphigus signature' could be summarized as follows: (i) a down-regulation of SCFA with anti-inflammatory functions, especially propionic and butyric acids and (ii) an up-regulation of pro-inflammatory MCFA and LCFA, including hexanoic and hexadecanoic acids.…”
Section: Discussionsupporting
confidence: 52%
“…21 Our group have recently observed changes in the profiles of circulating FFA in various immune-mediated disorders, such as celiac disease, 19 systemic sclerosis 22 and Crohn's disease. 23 Likewise, our data have shown that the serum FFA signature in PV patients is significantly altered in comparison with the 'healthy profile' and displayed a shift towards a pro-inflammatory state. This 'pemphigus signature' could be summarized as follows: (i) a down-regulation of SCFA with anti-inflammatory functions, especially propionic and butyric acids and (ii) an up-regulation of pro-inflammatory MCFA and LCFA, including hexanoic and hexadecanoic acids.…”
Section: Discussionsupporting
confidence: 52%
“…НВК та ХК -не смертельні захворювання, але дуже виснажливі, з широким спектром симптомів, які містять лихоманку, ректальні кровотечі, блювання, діарею, біль у животі, анемію та втрату маси тіла. Хронічний характер симптомів призводить до зниження якості життя таких пацієнтів [1][2][3].…”
Section: вступunclassified
“…Жирні кислоти (ЖК) -це карбонові кислоти з аліфатичним ланцюгом, які залежно від довжини ланцюга класифікуються як коротко-, середньо-та довголанцюгові ЖК (КЛЖК, СЛЖК та ДЛЖК відповідно), а залежності від кількості подвійних зв'язків у ньому як насичені ЖК (НЖК) -без подвійних зв'язків, мононенасичені ЖК (МНЖК) -з одним подвійним зв'язком та поліненасичені ЖК (ПНЖК) -з двома або більше подвійними зв'язками [1,2,5]. До КЛЖК (C:2-C:5), які мають не більше ніж 5 атомів вуглецю у своєму складі, належать летка оцтова (C2:0), пропіонова (C3:0) та масляна (C4:0) ЖК [5].…”
Section: вступunclassified
See 1 more Smart Citation
“…Primer trimming, denoising, high-quality sequence merging and ASV delineation were performed using Cutadapt and DADA2 in the QIIME2 v2021.4 environment. The scikit-learn classifier retrained on the V3-V4 region of the SILVA138 database has been used for the taxonomic assignment [24]. Further details regarding sequence processing and analysis is available on GitHub (see https://github.com/LeandroD94/Papers).…”
Section: Feces Collection and 16s Rrna V3-v4 Region Gene Sequencing A...mentioning
confidence: 99%